The Implementation of Ice-Breaking Activities in English Classroom - Adi F. Mahmud; Abudar Yusup; Amrin Saban (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
This study attempts to identify and explore high school students' perceptions of using ice-breaking activities in the English classroom. A qualitative method with a descriptive qualitative design. The study was done at SMA Al-Irsad Kota Ternate Jl. Perumnas South Ternate District and it involved second-grade students as subjects. They totaled 16 students, which consisted of 9 males and 7 females. Questionnaire and an unstructured interview were used to collect the data. A questionnaire was distributed to students in the classroom, and they filled it out in 60 minutes. The questions consisted of 10 statements. After the Questionnaire distribution, the students were interviewed based on the interview guidelines provided by the researchers. The interview was done with students who had already filled out the questionnaire. Data from the questionnaire were analyzed with a 5-point Likert scale (1=strongly disagree; 2 = disagree; 3 = neutral; 4 = agree; and 5 = strongly agree) to measure students' perceptions of ice-breaking activities in the English classroom. A 5-point Likert scale was counted with a frequency and percentage formula. During the interview, the data is analyzed through four steps: (1) data reduction, (2) coding, (3) data display, and (4) concluding. Results of the study showed that (1) 16 students have the same perception of the implementation of ice-breaking activities in English class; (2) all students' perceptions of ice-breaking activities are very positive; (3) ice-breaking activities are necessary and very needed for application in English class; and (4) students' perceptions of ice-breaking activities include helping students join the learning process, eliminating saturation, creating a positive learning atmosphere in the class, improving students’ interest and motivation, and increasing students' learning achievement.